2004
DOI: 10.1038/sj.bjc.6602273
|View full text |Cite
|
Sign up to set email alerts
|

The risk of cancer in HIV-infected people in southeast England: a cohort study

Abstract: This study used data from the Communicable Disease Surveillance Centre's national HIV database and the Thames Cancer Registry to assess the risk of cancer in HIV-infected people in southeast England. Among 26 080 HIV-infected men with 158 660 person-years follow-up, 1851 cancers, and among 7110 HIV-infected women (31 098 person-years), 171 cancers were identified. The standardised incidence ratio (SIR) for all non-AIDS-defining cancers was significantly increased in HIV-infected men (2.8, 95% confidence interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
2
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 14 publications
4
70
2
1
Order By: Relevance
“…Some studies have not demonstrated an association of AIDS diagnoses or CD41 cell counts with lung cancer risk, arguing against a major effect of immunosuppression (18,32,33,41,49). However, several other studies have reported increased lung cancer risk among HIV-infected persons with advanced immune suppression, evaluated as a prior AIDS diagnosis or lower CD41 cell counts compared with those HIV-infected persons with relatively intact immune function (4,22,32). In a recent analysis of a large database of HIV-infected persons cared for in French hospitals (36), a clear dose-response relationship between declining current CD41 cell counts and lung cancer risk was observed.…”
Section: Role Of Immunosuppression Hiv Viral Load and Artmentioning
confidence: 99%
“…Some studies have not demonstrated an association of AIDS diagnoses or CD41 cell counts with lung cancer risk, arguing against a major effect of immunosuppression (18,32,33,41,49). However, several other studies have reported increased lung cancer risk among HIV-infected persons with advanced immune suppression, evaluated as a prior AIDS diagnosis or lower CD41 cell counts compared with those HIV-infected persons with relatively intact immune function (4,22,32). In a recent analysis of a large database of HIV-infected persons cared for in French hospitals (36), a clear dose-response relationship between declining current CD41 cell counts and lung cancer risk was observed.…”
Section: Role Of Immunosuppression Hiv Viral Load and Artmentioning
confidence: 99%
“…The incidence of CNS involvement has been suggested to be higher in ARL compared to the HIV-negative patients with NHL [23,75] and this may reflect the more advanced stage at presentation or adverse features. Although there is no reported increase in incidence of secondary CNS lymphoma in the HIV setting, there have been no specific studies that have addressed this in a randomized setting.…”
Section: Prevention Of Secondary Cns Lymphomamentioning
confidence: 99%
“…Opportunistic infections are the most common manifestation, although sudden progression of existing KS or development of new lesions may also occur [73][74][75][76]. A systematic review identified 54 cohort studies of 13 103 patients starting HAART, of whom 1699 developed IRIS, 6.4% of whom had KS [77].…”
Section: Haartmentioning
confidence: 99%
“…Moreover, musculoskeletal sarcomas are rarely mentioned separately in NADC reports. 13 Newnham et al reported five soft tissue sarcomas and one bone sarcoma with the SIR (standardised incidence ratio) for soft tissue tumours being 3.6 and for skeletal malignancies 1.5. The specific histology of these sarcomas and their site was unfortunately not described, and it remains unclear if these included any of the sarcomas that we reported in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The specific histology of these sarcomas and their site was unfortunately not described, and it remains unclear if these included any of the sarcomas that we reported in our study. 13 A study by Bhatia et al identified a total of 176 non-Kaposi's sarcomas in immune compromised patients in the SEER database, 75 in people with HIV/Aids and 101 in transplant recipients. Leiomyosarcomas (n = 101) were the most frequently reported sarcomas, followed by angiosarcomas (n = 23) and fibrohistiocytic tumours (n = 17).…”
Section: Discussionmentioning
confidence: 99%